Cooperative spectrum sensing of cognitive radio - Tran, Nhu Hai. (2012)
Recently, the concept of cognitive radio has been introduced to overcome the shortage of frequency spectrum, due to the rapid development of telecommunication technology and the policy of fixed-spectrum assignment, which emerged over the last one hundred years. Spectrum sensing is the key function that enables the deployment of cognitive radio network, by actively detecting primary users’ signals. In the early stage of development, spectrum sensing is done by a single cognitive radio based on some well-known technique such as matched filter, energy detection and cyclo-stationary. However, such techniques are often suffered from the fading or shadowing channel problem. Therefore, cooperative spectrum sensing is proposed to mitigate the effects of disturbed channel condition. In the report, first the most prevalent single sensing technique, energy detection, is discussed. Then, it is dedicated to investigate two approaches of cognitive spectrum sensing, which are soft combination and hard combination. The report shows that the cooperative spectrum sensing has better performance as compared to single spectrum sensing; nevertheless, it is also more complicated. Although, soft combination cooperative sensing shows its superiority to that of hard combination in terms of performance, it also requires more complexity. Currently, the optimum method for soft-combination has been found, yet such a method for hard-combination has not been proposed. Therefore, in the future, more research should focus on that.